VD_FINDINFO HC / 2015 / 112 vom 26. November 2014 - VD Tribunal cantonal (2014)
ACTION EN DIVORCE, DROIT DE GARDE, EXPERTISE PSYCHIATRIQUE, OBLIGATION D'ENTRETIEN, ENFANT | 133 al. 1 CC, 133 al. 2 CC, 133 CC, 157 CPC (CH)